A modified polyurea resin for electrode plate, preparation method and application thereof, binder, electrode plate, preparation method of electrode plate, lithium battery

By using modified polyurea resin as a binder in lithium batteries and forming a multi-dimensional network structure by grafting multiple units, the stress problem caused by volume expansion of silicon-based negative electrode materials during charge and discharge cycle is solved, and the circulation and safety performance of lithium batteries are significantly improved.

CN118852543BActive Publication Date: 2025-03-21CYG NEW ENERGY MATERIAL RESEARCH INSTITUTE (GUANGDONG) CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411324355.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-09-23
Publication Date
2025-03-21
Estimated Expiration
2044-09-23

AI Technical Summary

Technical Problem

In existing lithium batteries, the volume expansion of the silicon-based negative electrode material leads to increased stress during the charge and discharge cycle, resulting in cracking and powdering of the material, and poor battery circulation performance, limiting the use of silicon-based negative electrode material.

Method used

Modified polyurea resin is used as the binder, and acrylonitrile, acrylic and organosiloxane units are grafted on the main chain of the aqueous polyurea resin to form a multi-dimensional network structure, enhance the bonding force and mechanical strength, and inhibit the expansion of the silicon-based negative electrode.

Benefits of technology

The circulation performance of lithium batteries is significantly improved. The first Coulomb efficiency can reach 89.5-90.5%, the full-electric expansion rate is as low as 27.0-29.2%, and the capacity retention rate of 500 cycles can reach 84.6-88.9%, which extends the service life of the battery and improves safety performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The present invention belongs to the technical field of polymer materials, and provides a modified polyurea resin for electrode plates, a preparation method and application thereof, a binder, an electrode plate, a preparation method of an electrode plate, and a lithium battery. The modified polyurea resin for electrode plates provided by the present invention uses a water-based polyurea resin containing carbon-carbon double bonds as the main chain, and connects acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds on the main chain through chemical bonds. The modified polyurea resin for electrode plates provided by the present invention is further used as a binder to prepare negative electrode plates, thereby enhancing the mechanical strength of the negative electrode plates, effectively inhibiting the volume expansion of silicon particles, buffering the mechanical stress during the volume expansion of silicon, and significantly improving the cycle performance of lithium batteries. There are very obvious improvements in peel strength, first coulomb efficiency, full charge expansion and cycle retention rate, effectively extending the service life of lithium batteries and improving the safety performance of lithium batteries.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of polymer materials, and more specifically, to a modified polyurea resin for an electrode plate, a preparation method and application thereof, a binder, an electrode plate, a preparation method of an electrode plate, and a lithium battery. Background Art

[0002] Nowadays, secondary batteries, especially lithium batteries, have been widely used in mobile phones, laptops, portable electronic devices, new energy vehicles, energy storage and other fields. At present, the negative electrode material of commercial lithium batteries is mainly graphite. The actual specific capacity of graphite negative electrode material is 360mAh / g, which is close to its theoretical value (372mAh / g), so it is difficult to further improve the energy density of lithium batteries. Therefore, it is necessary to develop negative electrode materials with higher theoretical capacity. Silicon materials have become one of the most studied and most promising high-capacity negative electrode materials with extremely high theoretical lithium storage capacity (up to 4200mAh / g) and abundant reserves and low cost. Researchers increase the specific capacity of the negative electrode by adding high-capacity active materials such as silicon to graphite. However, the volume of silicon-based materials expands by up to 300-400% during the charge and discharge cycle process, which will generate great stress inside the battery, causing the negative electrode material to crack and pulverize, the battery cell capacity to decay quickly, and the cycle performance to be poor, which seriously limits the use of silicon-based negative electrode materials in lithium batteries.

[0003] As a key part of the electrode structure, the binder provides the electrodes with an interconnected structure and mechanical strength, maintains the electron / ion transfer during the battery cycle, and plays a vital role in the overall electrochemical performance. Therefore, adjusting the binder is one of the solutions to solve the electrode expansion. The binders commonly used in silicon-based negative electrode materials in the prior art include SBR (styrene-butadiene rubber) binders and PAA (polyacrylic acid) binders. SBR binders usually need to be used in conjunction with carboxymethyl cellulose (CMC). However, SBR itself has low strength, poor adhesion, and poor inhibition of electrode expansion. Therefore, when used in silicon-based negative electrodes, its cycle performance is often very poor; while the electrodes prepared with PAA binders have poor cycle performance and insufficient flexibility.

[0004] Therefore, a negative electrode binder with high bonding strength and the ability to reduce the expansion of silicon-based negative electrodes is developed to ensure the flexibility of high-capacity negative electrode materials and the cycle stability of the resulting lithium batteries. Summary of the invention

[0005] The present invention aims to solve at least one of the technical problems existing in the above-mentioned prior art. To this end, the present invention proposes a modified polyurea resin for electrode plates and its preparation method and application, a binder, an electrode plate, a method for preparing an electrode plate, and a lithium battery. The modified polyurea resin for electrode plates provided by the present invention has excellent bonding properties and can be used as a binder for preparing negative electrode plates. It can significantly inhibit the expansion of silicon-based negative electrodes, while giving the negative electrode plates excellent flexibility. Further preparation of lithium batteries can improve the cycle performance of the battery. The first coulomb efficiency of the lithium battery can reach 89.5-90.5%, the full-charge expansion rate is as low as 27.0-29.2%, and the capacity retention rate of 500 cycles can reach 84.6-88.9%. There are very obvious improvements in peel strength, first coulomb efficiency, full-charge expansion and cycle retention rate.

[0006] A first aspect of the present invention provides a modified polyurea resin for an electrode plate.

[0007] Specifically, a modified polyurea resin for an electrode plate comprises a main chain and a graft unit, wherein the graft unit is grafted onto the main chain through a chemical bond, wherein the main chain is a water-based polyurea resin containing a carbon-carbon double bond, and the graft unit comprises an acrylonitrile graft unit, an acrylic graft unit and an organic siloxane unit containing a carbon-carbon double bond;

[0008] The aqueous polyurea resin containing carbon-carbon double bonds includes the following preparation raw materials in parts by weight:

[0009] 10-150 parts of aliphatic polyamines,

[0010] Aromatic isocyanate 10-80 parts,

[0011] 2-30 parts of hydrophilic chain extender,

[0012] 2-20 parts of a capping agent containing a carbon-carbon double bond,

[0013] Neutralizer 2-30 parts.

[0014] The modified polyurea resin for electrode plates provided by the present invention uses a water-based polyurea resin containing carbon-carbon double bonds as the main chain structure, and utilizes the double bonds on the main chain to covalently connect with the grafting units, and the grafting units include acrylonitrile grafting units, acrylic grafting units and organic siloxane units containing carbon-carbon double bonds. Among them, the acrylonitrile grafting unit has good wettability with the electrolyte and good electrochemical stability; the -CN group therein can form hydrogen bonds or chemical bonds with silicon particles, thereby improving the bonding force, while reducing the expansion of the silicon-based negative electrode and greatly improving its cycle life. The acrylic grafting unit can assist lithium ion conduction, increase the ion migration rate, and improve the fast charging performance and low temperature performance of the system. The alkoxy group -OR contained in the organic siloxane unit containing carbon-carbon double bonds can be hydrolyzed into -OH, and can form strong physical or chemical forces such as hydrogen bonds, ionic bonds or chemical bonds with silicon particles with -OH on the surface of the negative electrode, thereby achieving multi-dimensional bonding of silicon particles and forming a multi-dimensional network three-dimensional structure, so it has good adhesion, excellent effect of inhibiting silicon expansion, can effectively enhance the mechanical strength of the negative electrode, buffer the mechanical stress during the silicon volume expansion process, and significantly improve the cycle performance of the lithium battery. The negative electrode binder further prepared by the modified polyurea resin for the electrode plate provided by the present invention has strong bonding performance, and the strong physical and chemical effects of the negative electrode binder enhance the mechanical strength of the negative electrode, can effectively inhibit the volume expansion of silicon particles, buffer the mechanical stress during the silicon volume expansion process, reduce the solid electrolyte intermediate phase (SEI film) produced by the contact reaction of silicon with the electrolyte during the continuous expansion process, effectively eliminate the side reactions caused by the unstable solid electrolyte intermediate phase, significantly improve the cycle performance of the lithium battery, effectively extend the service life of the lithium battery, and improve the safety performance of the lithium battery.

[0015] Preferably, the waterborne polyurea resin containing carbon-carbon double bonds comprises the following preparation raw materials: aliphatic polyamine, aromatic isocyanate, hydrophilic chain extender, end-capping agent containing carbon-carbon double bonds and neutralizing agent.

[0016] On the one hand, aromatic isocyanates can provide the toughness (rigidity) required by the binder, maintain the mechanical strength required by the binder, and help improve the binder's tolerance to the electrolyte, ensure the integrity of the binder, and thus maintain the integrity of the overall structure of the pole piece. On the other hand, aliphatic polyamines can provide the flexibility required by the binder to prevent the pole piece from brittle fracture and failure during processing. In addition, they can also improve the binder's ability to wet the substrate, thereby improving the bonding force between the binder and the substrate. At the same time, they can also give the binder a certain electrolyte swelling property, increase the rate of lithium ion transmission, and thus help reduce the impedance of the pole piece. The water-based polyurea resin containing carbon-carbon double bonds used in the present invention includes a rigid segment (aromatic isocyanate group) and a flexible segment (aliphatic polyamine), and thus has excellent flexibility and bonding properties, further making the modified polyurea resin for the electrode plate have a certain flexibility, thereby giving the negative electrode plate excellent flexibility, effectively inhibiting the huge volume change of silicon particles, and effectively maintaining the bonding between the active material and the current collector, which can effectively reduce the internal resistance of the negative electrode plate, inhibit the expansion of the plate, effectively extend the service life of the battery, and help improve the cycle performance of the battery. Furthermore, the water-based polyurea resin containing carbon-carbon double bonds contains both hydrophobic benzene-containing segments and hydrophilic ether-containing segments, so it can simultaneously achieve bonding of hydrophobic graphite particles and hydrophilic silicon particles, thereby improving the bonding performance.

[0017] Preferably, the number of atoms other than hydrogen atoms on the main chain of the aliphatic polyamine is greater than 5. The aliphatic polyamine with a suitable chain length is conducive to giving the binder better flexibility.

[0018] Preferably, the aliphatic polyamine is an aliphatic carbon chain diamine and / or an aliphatic ether diamine.

[0019] Preferably, the aliphatic carbon chain diamine is at least one of 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,36-triacontanediamine, and 2,5-dimethyl-1,6-hexanediamine.

[0020] Preferably, the aliphatic ether-based diamine is at least one of bis(2-aminoethyl)ether, 3,6-dioxa-1,8-octanediamine, 4,7-dioxa-1,10-decanediamine, 4,7-dioxa-2,9-decanediamine, 4,9-dioxa-1,12-dodecanediamine, 5,8-dioxa-3,10-dodecanediamine, 4,7,10-trioxa-1,13-tridecanediamine, bis(3-aminopropyl)polytetrahydrofuran, and polyoxyalkylene diamine (such as the following polyoxyalkylene diamines from Huntsman: Jeffamine® D230, Jeffamine® D400, Jeffamine® D2000, Jeffamine® D4000, Jeffamine® ED600, Jeffamine® ED900, and Jeffamine® ED2003).

[0021] Preferably, the aromatic isocyanate is at least one of 4,4′-diphenylmethane diisocyanate (MDI), toluene diisocyanate (TDI), p-xylylene diisocyanate (p-XDI), p-phenylene diisocyanate (PPDI), dimethylbiphenyl diisocyanate (TODI), 1,5-naphthalene diisocyanate (NDI), 3,3′-dimethoxy-4,4′-diphenyl diisocyanate (DADI), 2,4-ethylphenyl diisocyanate (EDI), and 3,3-dichlorobiphenyl-4,4′-diisocyanate.

[0022] Preferably, the hydrophilic chain extender is at least one of 2-carboxy-1,4-phenylenediamine, 2-amino-5-guanidine valeric acid (arginine), 2,6-diaminohexanoic acid (lysine), and 2-amino-3-(4-imidazolyl) propionic acid (histidine).

[0023] Preferably, the capping agent containing a carbon-carbon double bond is at least one of m-isopropenyl-α,α-dimethylphenyl isocyanate (m-TMI), 2-aminoethyl acrylate, and 2-aminoethyl methacrylate.

[0024] Preferably, the neutralizing agent is at least one of sodium hydroxide, lithium hydroxide, potassium hydroxide, ammonia water, triethylamine, and dimethylethanolamine.

[0025] Preferably, the weight content of double bonds in the aqueous polyurea resin containing carbon-carbon double bonds is 5-50%.

[0026] The "weight content of double bonds" in the waterborne polyurea resin containing carbon-carbon double bonds refers to: (1) when the end-capping agent containing carbon-carbon double bonds is m-isopropenyl-α,α-dimethylphenyl isocyanate (m-TMI), the "weight content of double bonds" is the weight ratio of the end-capping agent containing carbon-carbon double bonds to the aliphatic polyamine; (2) when the end-capping agent containing carbon-carbon double bonds is 2-aminoethyl acrylate and / or 2-aminoethyl methacrylate, the "weight content of double bonds" is the weight ratio of the end-capping agent containing carbon-carbon double bonds to the aromatic isocyanate. The present invention uses the end-capping agent containing carbon-carbon double bonds to react with amino groups or with isocyanate groups, thereby introducing double bonds into the polyurea chain segments, and controlling the double bond content in the waterborne polyurea resin containing carbon-carbon double bonds by controlling the amount of the end-capping agent containing carbon-carbon double bonds, thereby preventing the subsequent graft polymerization reaction of the waterborne polyurea resin containing carbon-carbon double bonds from being affected by excessive or insufficient double bond content.

[0027] A second aspect of the present invention provides a method for preparing a modified polyurea resin for an electrode plate.

[0028] A method for preparing a modified polyurea resin for an electrode plate comprises the following steps:

[0029] Mixing an aqueous polyurea resin emulsion containing carbon-carbon double bonds, an acrylonitrile monomer, an acrylic monomer, a silane coupling agent, an emulsifier and an initiator to cause a polymerization reaction to obtain the modified polyurea resin for the electrode plate;

[0030] The aqueous polyurea resin containing carbon-carbon double bonds includes the following preparation raw materials in parts by weight:

[0031] 10-150 parts of aliphatic polyamines,

[0032] Aromatic isocyanate 10-80 parts,

[0033] 2-30 parts of hydrophilic chain extender,

[0034] 2-20 parts of a capping agent containing a carbon-carbon double bond,

[0035] Neutralizer 2-30 parts.

[0036] Preferably, the modified polyurea resin for electrode plates includes the following preparation raw materials in parts by weight:

[0037] 5-40 parts of water-based polyurea resin emulsion containing carbon-carbon double bonds,

[0038] 5-40 parts of acrylonitrile monomer,

[0039] 5-50 parts of acrylic monomer,

[0040] Silane coupling agent 0.1-30 parts,

[0041] Emulsifier 0.1-5 parts,

[0042] Initiator 0.1-5 parts.

[0043] Preferably, the polymerization reaction temperature is 50-90° C., and / or the polymerization reaction time is 2-16 h.

[0044] The carbon-carbon double bonds in the waterborne polyurea resin containing carbon-carbon double bonds can undergo polymerization reaction with the carbon-carbon double bonds of acrylonitrile monomers, acrylic monomers, and silane coupling agents to be grafted together.

[0045] Preferably, acrylonitrile monomers, acrylic monomers, silane coupling agents, emulsifiers and initiators are added in batches. First, 5%-80% of the total amount of acrylonitrile monomers, acrylic monomers, silane coupling agents, emulsifiers are mixed with the aqueous polyurea resin emulsion containing carbon-carbon double bonds, and then 5%-80% of the initiator is added to cause polymerization reaction to obtain a prepolymer; then the remaining acrylonitrile monomers, acrylic monomers, silane coupling agents, and emulsifiers are added and mixed, and then the remaining initiator is added to continue the polymerization reaction to obtain the modified polyurea resin for the electrode plate.

[0046] Preferably, the acrylonitrile monomer is acrylonitrile and / or methacrylonitrile.

[0047] Preferably, the acrylic monomer is at least one of acrylic acid, methacrylic acid, lithium acrylate, lithium methacrylate, sodium acrylate, sodium methacrylate, potassium acrylate, and potassium methacrylate.

[0048] Further preferably, the acrylic monomer is lithium acrylate. The negative electrode binder contains lithium acrylate fragments, which can help lithium ion conduction, increase ion migration rate, and improve the fast charging performance and low temperature performance of the system.

[0049] Preferably, the silane coupling agent is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl triisopropoxysilane, allyl trimethoxysilane, methyl allyl trimethoxysilane, 3-(acryloxy) propyl trimethoxysilane, 3-(methacryloxy) propyl trimethoxysilane, 3-(acryloxy) propyl methyl dimethoxysilane, 3-(acryloxy) propyl triisopropoxysilane, 3-(acryloxy) propyl methyl diisopropoxysilane, γ-acryloxy propyl tris(β-trimethoxyethoxysilane), 3-(methacryloxy) propyl trimethoxysilane, At least one of 3-(acryloyloxy)propylmethyldimethoxysilane, 3-(acryloyloxy)propyltriethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(acryloyloxy)propylmethyldiethoxysilane, 3-(methacryloyloxy)propylmethyldiethoxysilane, 3-(methacryloyloxy)propyltriisopropoxysilane, 3-(methacryloyloxy)propylmethyldiisopropoxysilane, γ-methacryloyloxypropyltris(trimethylsiloxy)silane, and γ-methacryloyloxypropyltris(β-trimethoxyethoxysilane).

[0050] Silane coupling agents contain carbon-carbon double bonds, and therefore can undergo polymerization reactions with acrylic monomers and acrylonitrile monomers. The formed carbon-carbon main chain has high mechanical strength and can maintain the stability of the electrode micro-skeleton structure. Silane coupling agents can also react with the double bonds of waterborne polyurea resins containing carbon-carbon double bonds to graft organic siloxane groups on the main chain of waterborne polyurea resins containing carbon-carbon double bonds. The alkoxy groups (-OR) therein can be hydrolyzed into hydroxyl groups, and can then form strong physical or chemical interactions such as hydrogen bonds, ionic bonds or chemical bonds with silicon particles with hydroxyl groups on the surface of the negative electrode, thereby achieving multi-dimensional bonding to the silicon particles. Therefore, the binder has strong bonding properties.

[0051] Preferably, the emulsifier is at least one of polypropylene alcohol, polypropylene pyrrolidone, allyl nonylphenol polyoxyethylene ether ammonium sulfate, sodium allyloxyhydroxysulfonate, sodium n-decyl sulfate, sodium dodecylbenzene sulfonate, and Span.

[0052] Preferably, the initiator is at least one of dibenzoyl peroxide, dilauroyl peroxide, di-tert-butyl peroxide, diisopropylbenzene peroxide, azobisisobutyronitrile, azobisisoheptylnitrile, potassium persulfate, sodium persulfate, and ammonium persulfate.

[0053] Preferably, the solid content of the aqueous polyurea resin emulsion containing carbon-carbon double bonds is 10-60%.

[0054] Preferably, the method for preparing the aqueous polyurea resin emulsion containing carbon-carbon double bonds comprises the following steps:

[0055] The aliphatic polyamine and the aromatic isocyanate are mixed and reacted, and then a hydrophilic chain extender is added to continue the reaction, and then a capping agent containing a carbon-carbon double bond is added for further reaction, and then a neutralizing agent is added to continue the reaction, and finally water is added for emulsification to obtain the aqueous polyurea resin emulsion containing a carbon-carbon double bond.

[0056] Preferably, the mixing reaction of the aliphatic polyamine and the aromatic isocyanate specifically comprises: firstly heating the aliphatic polyamine to 80-150° C., dehydrating the aliphatic polyamine under vacuum until no bubbles are generated in the reaction kettle, and then mixing the aliphatic polyamine with the aromatic isocyanate for reaction.

[0057] Preferably, the aliphatic polyamine and the aromatic isocyanate are mixed, reacted at 60-90°C for 1-8h, then a hydrophilic chain extender is added, and the reaction is continued at 60-90°C for 1-4h, and then a capping agent containing a carbon-carbon double bond is added, and the reaction is further continued at 60-90°C for 1-4h, then a neutralizing agent is added, and the reaction is continued at 35-45°C for 1-4h, and finally water is added for emulsification to obtain the aqueous polyurea resin emulsion containing carbon-carbon double bonds.

[0058] A third aspect of the present invention provides an application of a modified polyurea resin for an electrode plate.

[0059] The invention discloses an application of a modified polyurea resin for electrode plates in the preparation of adhesives, coatings, furniture and electronic products.

[0060] A fourth aspect of the present invention provides an adhesive.

[0061] A binder, the components of which include the modified polyurea resin for the electrode plate.

[0062] A fifth aspect of the present invention provides an electrode plate.

[0063] An electrode plate comprises a current collector and a coating, wherein the raw materials for preparing the coating comprise the binder, active material and conductive agent.

[0064] Preferably, the current collector is copper foil.

[0065] Preferably, in parts by weight, the raw materials for preparing the coating include: 0.5-10 parts of a binder, 50-100 parts of an active substance, and 0.5-5 parts of a conductive agent.

[0066] Preferably, the electrode plate is a negative electrode plate.

[0067] Preferably, the active material is a negative electrode active material, and / or the conductive agent is a negative electrode conductive agent.

[0068] Preferably, the negative electrode active material is at least one of natural graphite, artificial graphite, elemental silicon, silicon oxide, and silicon alloy.

[0069] Preferably, the negative electrode conductive agent is at least one of conductive graphite, conductive carbon black, carbon nanotubes (such as single-walled carbon nanotubes), and graphene.

[0070] A sixth aspect of the present invention provides a method for preparing an electrode plate.

[0071] A method for preparing an electrode sheet comprises the following steps:

[0072] The binder, active material, conductive agent and water are mixed to obtain electrode slurry, which is then coated on a current collector and dried to obtain a coating to obtain the electrode plate.

[0073] Preferably, the drying temperature is 110-130° C., and / or the drying time is 1-10 min.

[0074] A seventh aspect of the present invention provides a lithium battery.

[0075] A lithium battery comprises a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode is the electrode plate.

[0076] Preferably, the active material of the positive electrode is at least one of lithium cobalt oxide, lithium manganese oxide, lithium iron phosphate, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and lithium-rich manganese-based materials.

[0077] Preferably, the electrolyte contains at least one of lithium hexafluorophosphate (LiPF6), lithium bis(trifluoromethylsulfonyl)imide (LITFSI), and lithium bis(fluorosulfonyl)imide (LIFSI).

[0078] Preferably, the material of the diaphragm is one of a polyethylene (PE) diaphragm, a polypropylene (PP) diaphragm, and a multi-layer composite (PP / PE / PP multi-layer composite) diaphragm.

[0079] Compared with the prior art, the beneficial effects of the present invention are as follows:

[0080] The modified polyurea resin for electrode plates provided by the present invention uses a water-based polyurea resin containing carbon-carbon double bonds as the main chain, and graft units are connected to the main chain through chemical bonds. These graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds. The modified polyurea resin for electrode plates provided by the present invention has excellent bonding properties. It is further used as a binder to prepare negative electrode plates, and the peel strength can reach 17-28N / M, and it has excellent flexibility. The strong physical and chemical effects of the binder enhance the mechanical strength of the negative electrode plates, can effectively inhibit the volume expansion of silicon particles, buffer the mechanical stress during the volume expansion of silicon, reduce the contact reaction between silicon and electrolyte to produce a solid electrolyte intermediate phase during the continuous expansion process, effectively eliminate the side reactions caused by the unstable solid electrolyte intermediate phase, and significantly improve the cycle performance of the lithium battery. The first coulomb efficiency of the lithium battery can reach 89.5-90.5%, the full-charge expansion rate is as low as 27.0-29.2%, and the capacity retention rate after 500 cycles can reach 84.6-88.9%. There are very obvious improvements in peel strength, first coulomb efficiency, full-charge expansion and cycle retention rate, which effectively prolongs the service life of the lithium battery and improves the safety performance of the lithium battery. DETAILED DESCRIPTION

[0081] In order to make the technical scheme of the present invention more clearly understood by those skilled in the art, the following embodiments are listed for illustration. It should be pointed out that the following embodiments do not limit the protection scope of the present invention.

[0082] Unless otherwise specified, the raw materials, reagents or devices used in the following examples can be obtained from conventional commercial sources or by existing known methods.

[0083] Example 1

[0084] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0085] A method for preparing a modified polyurea resin for an electrode plate comprises the following steps:

[0086] 1. Preparation of water-based polyurea resin emulsion containing carbon-carbon double bonds: Add 60 parts of polyoxyalkyl diamine ED600 (number average molecular weight 600) into the reactor, heat to 115°C, dehydrate under vacuum for 2 hours until no bubbles are generated in the reactor, cool to 50°C, and seal the reactor. Then add 25 parts of 4,4′-diphenylmethane diisocyanate (MDI) into the reactor, introduce nitrogen into the reactor to isolate the air, and react at 60°C for 4 hours; then add 5 parts of 2-carboxy-1,4-phenylenediamine into the reactor for chain extension reaction for 3 hours; then add 12 parts of m-isopropenyl-α, α-dimethylphenyl isocyanate (m-TMI) for end-capping reaction for 3 hours; cool to about 40°C, add 3 parts of ammonia water and react for 2 hours; finally, add deionized water for emulsification to obtain an aqueous polyurea resin emulsion containing carbon-carbon double bonds, with a solid content of 40%, and a double bond weight content of 20% in the aqueous polyurea resin containing carbon-carbon double bonds.

[0087] 2. Preparation of modified polyurea resin for electrode plates:

[0088] (1) Add 10 parts of the aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared above into a reaction kettle, and then add 100 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane in sequence, and stir at a speed of 1000 rpm to form a uniform dispersion; introduce nitrogen to isolate the air, heat to 70°C, and then add 0.2 parts of ammonium persulfate, react for 2 hours, and obtain a primary product;

[0089] (2) 180 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane were mixed and stirred at a speed of 1000 rpm to obtain a pre-dispersed liquid, which was added dropwise to the reactor through a peristaltic pump for 4 hours. At the same time, 10 parts of an aqueous solution of ammonium persulfate with a mass concentration of 2wt% were added dropwise for 4.5 hours. After the addition was completed, the reaction temperature was maintained at 70°C for 2 hours. After the insulation was completed, deionized water and lithium hydroxide solution were added to adjust the solid content to 15% and the pH to neutral to obtain a modified polyurea resin for electrode plates.

[0090] Example 2

[0091] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0092] A method for preparing a modified polyurea resin for an electrode plate comprises the following steps:

[0093] 1. Preparation of water-based polyurea resin emulsion containing carbon-carbon double bonds: Add 90 parts of polyoxyalkylenediamine ED900 (number average molecular weight 900) into the reactor, heat to 115°C, dehydrate under vacuum for 2 hours until no bubbles are generated in the reactor, cool to 50°C, and seal the reactor. Then add 17.4 parts of 2,4-toluene diisocyanate (TDI) into the reactor, introduce nitrogen into the reactor to isolate the air, and react at 60°C for 5 hours; then add 4 parts of 2-amino-5-guanidine valeric acid into the reactor for chain extension reaction for 2 hours; then add 15 parts of m-isopropenyl-α, α-dimethylphenyl isocyanate (m-TMI) for end-capping reaction for 2 hours; cool to about 40°C, add 3 parts of ammonia water to react for 1.5 hours; finally, add deionized water for emulsification to obtain an aqueous polyurea resin emulsion containing carbon-carbon double bonds, with a solid content of 35%, and a double bond weight content of 16.7% in the aqueous polyurea resin containing carbon-carbon double bonds.

[0094] 2. Preparation of modified polyurea resin for electrode plates

[0095] (1) Add 10 parts of the aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared above into a reaction kettle, and then add 100 parts of deionized water, 0.1 parts of sodium allyloxyhydroxysulfonate, 15 parts of acrylonitrile monomer, 20 parts of methacrylic acid monomer, and 1 part of 3-(methacryloyloxy)propyltrimethoxysilane in sequence, and stir at a speed of 1000 rpm to form a uniform dispersion; introduce nitrogen to isolate the air, heat to 70°C, and then add 0.2 parts of ammonium persulfate, react for 2 hours, and obtain a primary product.

[0096] (2) 180 parts of deionized water, 0.1 parts of sodium allyloxyhydroxysulfonate, 15 parts of acrylonitrile monomer, 20 parts of methacrylic acid monomer, and 1 part of 3-(methacryloyloxy)propyltrimethoxysilane were mixed and stirred at a speed of 1000 rpm to obtain a pre-dispersed liquid, which was added dropwise to the reactor through a peristaltic pump for 4 hours. At the same time, 10 parts of a 2wt% ammonium persulfate aqueous solution were added dropwise for 4.5 hours. After the addition of the ammonium persulfate aqueous solution was completed, the reaction temperature was maintained at 70°C for 2 hours. After the insulation was completed, deionized water and lithium hydroxide solution were added to adjust the solid content to 15% and the pH to neutral to obtain a modified polyurea resin for electrode plates.

[0097] Example 3

[0098] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0099] A method for preparing a modified polyurea resin for an electrode plate comprises the following steps:

[0100] 1. Preparation of water-based polyurea resin emulsion containing carbon-carbon double bonds: Add 40 parts of polyoxyalkyl diamine D400 (number average molecular weight 400) into the reactor, heat to 115°C, dehydrate under vacuum for 2 hours until no bubbles are generated in the reactor, cool to 50°C, and seal the reactor. Then add 18.8 parts of p-xylene diisocyanate (p-XDI) into the reactor, introduce nitrogen into the reactor to isolate the air, and react at 60°C for 3.5 hours; then add 4 parts of 2,6-diaminohexanoic acid into the reactor for chain extension reaction for 2 hours; then add 10 parts of m-isopropenyl-α, α-dimethylphenyl isocyanate (m-TMI) for end-capping reaction for 3 hours; cool to about 40°C, add 5 parts of ammonia water to react for 1 hour; finally, add deionized water for emulsification to obtain an aqueous polyurea resin emulsion containing carbon-carbon double bonds, with a solid content of 42% and a double bond weight content of 25% in the aqueous polyurea resin containing carbon-carbon double bonds.

[0101] 2. Preparation of modified polyurea resin for electrode plates

[0102] (1) Add 10 parts of the aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared above into a reaction kettle, and then add 100 parts of deionized water, 0.1 parts of sodium n-decyl sulfate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane in sequence, and stir at a speed of 1000 rpm to form a uniform dispersion; introduce nitrogen to isolate the air, heat to 70°C, and then add 0.2 parts of ammonium persulfate, react for 2 hours, and obtain a primary product.

[0103] (2) 180 parts of deionized water, 0.1 parts of sodium n-decyl sulfate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane were mixed and stirred at a speed of 1000 rpm to obtain a pre-dispersed liquid, which was added dropwise to the reactor through a peristaltic pump for 4 hours. At the same time, 10 parts of a 2wt% ammonium persulfate aqueous solution were added dropwise for 4.5 hours. After the addition of the ammonium persulfate aqueous solution was completed, the reaction temperature was maintained at 70°C for 2 hours. After the insulation was completed, deionized water and lithium hydroxide solution were added to adjust the solid content to 15% and the pH to neutral to obtain a modified polyurea resin for electrode plates.

[0104] Example 4

[0105] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0106] A method for preparing a modified polyurea resin for an electrode plate comprises the following steps:

[0107] 1. Preparation of water-based polyurea resin emulsion containing carbon-carbon double bonds: 60 parts of polyoxyalkyl diamine ED600 (number average molecular weight 600) were added to the reactor, heated to 115°C, dehydrated under vacuum for 2 hours until no bubbles were generated in the reactor, cooled to 50°C, and the reactor was sealed. Then 16 parts of p-phenylene diisocyanate (PPDI) were added to the reactor, nitrogen was introduced into the reactor to isolate the air, and the reaction was carried out at 60°C for 6 hours; then 6 parts of 2,6-diaminocaproic acid were added to the reactor for chain extension reaction for 2 hours; then 5 parts of 2-aminoethyl acrylate were added for end-capping reaction for 2 hours; the temperature was lowered to about 40°C, 5 parts of triethylamine were added for reaction for 1 hour; finally, deionized water was added for emulsification to obtain a water-based polyurea resin emulsion containing carbon-carbon double bonds, with a solid content of 35%, and a double bond weight content of 31.2% in the water-based polyurea resin containing carbon-carbon double bonds.

[0108] 2. Preparation of modified polyurea resin for electrode plates

[0109] (1) Add 10 parts of the aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared above into a reaction kettle, and then add 100 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of vinyltrimethoxysilane in sequence, and stir at a speed of 1000 rpm to form a uniform dispersion; introduce nitrogen to isolate the air, heat to 70°C, and then add 0.2 parts of ammonium persulfate, react for 2 hours, and obtain a primary product.

[0110] (2) 180 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of vinyl trimethoxysilane were mixed and stirred at a speed of 1000 rpm to obtain a pre-dispersed liquid, which was added dropwise to the reactor through a peristaltic pump for 4 hours. At the same time, 10 parts of a 2wt% ammonium persulfate aqueous solution were added dropwise for 4.5 hours. After the addition of the ammonium persulfate aqueous solution was completed, the reaction temperature was maintained at 70°C for 2 hours. After the insulation was completed, deionized water and lithium hydroxide solution were added to adjust the solid content to 15% and the pH to neutral to obtain a modified polyurea resin for electrode plates.

[0111] Example 5

[0112] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0113] A method for preparing a modified polyurea resin for an electrode plate, which differs from Example 1 in that 3-(acryloxy)propyltrimethoxysilane is replaced with an equal weight of 3-(acryloxy)propylmethyldimethoxysilane, and other raw materials, amounts and preparation methods are the same as those in Example 1.

[0114] Example 6

[0115] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0116] A method for preparing a modified polyurea resin for an electrode plate, which differs from Example 1 only in that 3-(acryloxy)propyltrimethoxysilane is replaced with an equal weight of 3-(acryloxy)propyltriethoxysilane, and other raw materials, amounts and preparation methods are the same as those in Example 1.

[0117] Example 7

[0118] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0119] A method for preparing a modified polyurea resin for an electrode plate, which differs from Example 1 only in that, in the process of "preparing a modified polyurea resin for an electrode plate", the amount of 1 part of 3-(acryloxy)propyltrimethoxysilane in the initial product raw material component of step (1) and the amount of 1 part of 3-(acryloxy)propyltrimethoxysilane in step (2) are each increased to 3 parts (i.e., a total of 6 parts of 3-(acryloxy)propyltrimethoxysilane are used), and other raw materials, amounts and preparation methods are the same as in Example 1.

[0120] Example 8

[0121] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0122] A method for preparing a modified polyurea resin for an electrode plate is different from Example 1 only in that acrylonitrile is replaced by an equal weight of methacrylonitrile, and other raw materials, amounts and preparation methods are the same as those in Example 1.

[0123] Example 9

[0124] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0125] A method for preparing a modified polyurea resin for an electrode plate is different from Example 1 only in that 60 parts of polyoxyalkylenediamine ED600 are replaced by 15 parts of 3,6-dioxa-1,8-octanediamine, and other raw materials, amounts and preparation methods are the same as those in Example 1.

[0126] Example 10

[0127] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0128] A method for preparing a modified polyurea resin for an electrode plate, which differs from Example 1 only in that 60 parts of polyoxyalkylenediamine ED600 are replaced by 22 parts of 4,7,10-trioxa-1,13-tridecanediamine, and other raw materials, amounts and preparation methods are the same as those in Example 1.

[0129] Embodiment 11

[0130] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0131] A modified polyurea resin for an electrode plate is different from Example 1 only in that 60 parts of polyoxyalkylenediamine ED600 are replaced by 10.8 parts of p-phenylenediamine, and other substances, amounts and preparation methods are the same as those in Example 1.

[0132] Example 12

[0133] A modified polyurea resin for electrode plates comprises a main chain and graft units, wherein the graft units are grafted onto the main chain through chemical bonds, the main chain is an aqueous polyurea resin containing carbon-carbon double bonds, and the graft units include acrylonitrile graft units, acrylic acid graft units and organic siloxane units containing carbon-carbon double bonds.

[0134] A modified polyurea resin for an electrode plate, which differs from Example 1 only in that 4,4′-diphenylmethane diisocyanate (MDI) is replaced by 16.8 parts of hexamethylene diisocyanate (HDI), and other substances, amounts and preparation methods are the same as those in Example 1.

[0135] Comparative Example 1 (without polyurea resin main chain)

[0136] An acrylic resin emulsion, the preparation method of which is as follows:

[0137] (1) In a reaction kettle, add 100 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane in sequence, and stir at a speed of 1000 rpm to form a uniform dispersion; introduce nitrogen to isolate the air, heat to 70°C, then add 0.2 parts of ammonium persulfate, react for 2 hours, and obtain a primary product;

[0138] (2) 180 parts of deionized water, 0.1 parts of sodium dodecylbenzene sulfonate, 15 parts of acrylonitrile monomer, 20 parts of acrylic acid monomer, and 1 part of 3-(acryloyloxy)propyltrimethoxysilane were mixed and stirred at a speed of 1000 rpm to obtain a pre-dispersion liquid, which was added dropwise to the reactor through a peristaltic pump for 4 hours. At the same time, 10 parts of an ammonium persulfate aqueous solution with a mass concentration of 2wt% were added dropwise for 4.5 hours. After the addition of the ammonium persulfate aqueous solution was completed, the reaction temperature was maintained at 70°C for 2 hours. After the insulation was completed, deionized water and lithium hydroxide solution were added to adjust the solid content to 15% and the pH to neutral to obtain an acrylic resin emulsion.

[0139] Comparative Example 2

[0140] A modified polyurea resin for an electrode plate is prepared by directly mixing 10 parts of an aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared in Example 1 and an acrylic emulsion prepared in Comparative Example 1 (without grafting reaction) to prepare a modified polyurea resin for an electrode plate.

[0141] Comparative Example 3

[0142] A modified polyurea resin for an electrode plate, which differs from Example 1 only in that 3-(acryloxy)propyltrimethoxysilane (i.e., an organic siloxane unit without a carbon-carbon double bond) is not added during the preparation of the modified polyurea resin for an electrode plate, and other substances, amounts used and preparation methods are the same as those in Example 1.

[0143] Comparative Example 4

[0144] A modified polyurea resin for an electrode plate is prepared by directly blending the modified polyurea resin for an electrode plate prepared in Comparative Example 3 with 2 parts of 3-(acryloyloxy)propyltrimethoxysilane (without grafting reaction).

[0145] Comparative Example 5

[0146] A polyurea resin, specifically the aqueous polyurea resin emulsion containing carbon-carbon double bonds prepared in Example 1 (ie, without grafted side chain structure).

[0147] Comparative Example 6

[0148] Commercially available styrene butadiene rubber (SBR).

[0149] Product effect testing

[0150] 1. The modified polyurea resin for the electrode plates prepared in each embodiment and the material prepared in the comparative example are used as binders for silicon-based negative electrode materials to further prepare negative electrode plates. Among them, when the commercially available styrene-butadiene rubber SBR of comparative example 6 is used as a binder, it is necessary to mix styrene-butadiene rubber with sodium carboxymethyl cellulose (CMC) in a weight ratio of 1:1. The specific preparation process of the negative electrode plate is as follows: each binder is mixed with a silicon-carbon composite material (the silicon-carbon composite material uses a silicon-based / graphite composite negative electrode material with a gram capacity of 700mAh / g), conductive carbon black, and single-walled carbon nanotubes, wherein the mass ratio of silicon-carbon composite material, conductive carbon black, single-walled carbon nanotubes and binder (based on the mass of solids in the binder) is 92:0.5:0.5:7, and an appropriate amount of deionized water is added according to a total solid content of 40% to prepare a battery plate slurry. The uniformly dispersed battery electrode slurry was passed through a 100-mesh screen and coated on a 10 μm thick copper foil as a current collector. After drying at 120 °C for 5 min, the slurry was heated to 10 × 10 4 The negative electrode sheet is obtained by rolling with a unit length load of N / m.

[0151] 2. The negative electrode sheets prepared as above were respectively used, with nickel cobalt manganese oxide NCM622 as the positive electrode, a mixture of ethylene carbonate (EC), ethyl methyl carbonate (EMC), and diethyl carbonate (DEC) in a mass ratio of 1:1:1 as the solvent, 1 mol / L LiPF6 as the electrolyte, and polypropylene (PP) material as the separator to make soft-pack lithium batteries.

[0152] 3. The performance of the negative electrode sheet and the soft-pack lithium battery prepared above were tested respectively, and the test method was as follows:

[0153] (1) Peel strength: Cut the negative electrode into 2 cm × 10 cm strip test specimens, adhere the electrode to the side to be tested with 3M double-sided tape, and compact it with a roller to make it fit the electrode completely; then stick the other side of the double-sided tape to the surface of the stainless steel plate, bend one end of the specimen in the opposite direction with a bending angle of 180 degrees, and use a universal material testing machine to clamp the specimen and the stainless steel plate respectively for stretching, and record the force required for stretching in real time. Repeat the test 3 times and take the average value, which is the peel strength of the negative electrode.

[0154] (2) Flexibility of negative electrode sheet: A core rod with a diameter of Φ = 3 mm was placed on the current collector side of the rolled electrode sheet made of the binder prepared in the embodiment and the comparative example, and a bending test was performed. The state of the electrode sheet at this time was observed under an optical microscope. A good electrode sheet was marked as "○", and one that fell off or cracked was marked as "×".

[0155] (3) First coulombic efficiency of lithium battery: At 25°C, in the voltage range of 2.5-4.2V, the charge and discharge cycle is carried out at 0.33C. The first coulombic efficiency of the charge and discharge cycle is tested by the constant current method. The first coulombic efficiency is calculated according to the following formula ①:

[0156] First coulombic efficiency = charging capacity / discharging capacity × 100% Formula ①.

[0157] (4) Full charge expansion rate: At 25°C, within the voltage range of 2.5-4.2V, and after two charge and discharge cycles at 0.33C, fully charge the battery, disassemble the battery cell in the glove box, take out the negative electrode plate, clean the surface of the negative electrode plate with dimethyl carbonate (DMC) solvent and dry it, and measure the thickness of different areas of the plate with a spiral micrometer. The average value is d2. The original average thickness of the negative electrode plate is d1 (before assembling the battery, the thickness of different areas of the plate must be measured first, and then the average value is taken as d1). The full charge expansion rate is calculated according to the following formula ②:

[0158] Full charge expansion rate = (d2-d1) / d1×100% Formula ②.

[0159] (5) 500 cycle capacity retention rate: At 25°C, in the voltage range of 2.5-4.2V, the lithium battery after capacity conversion was charged to 4.2V at a constant current of 1C, then charged to a cut-off current of 0.05C at a constant voltage, left for 5 min, then discharged to 2.5V at a constant current of 1C, left for 5 min, and the discharge capacity after the first cycle was recorded; again, the battery was charged to 4.2V at a constant current of 1C, then charged to a cut-off current of 0.05C at a constant voltage, left for 5 min, then discharged to 2.5V at a constant current of 1C, left for 5 min, and this cycle was repeated 500 times, and the discharge capacity after the 500th cycle was recorded. The capacity retention rate was calculated according to the following formula ③:

[0160] Capacity retention rate = 500th discharge capacity / 1st discharge capacity × 100% Formula ③.

[0161] 4. The test results of the above items are shown in the following table:

[0162] Table 1 Performance test results of negative electrode sheets and soft-pack lithium batteries prepared by binders of various embodiments and comparative examples

[0163]

[0164] As can be seen from the above table, compared with the commercially available styrene-butadiene rubber SBR in Comparative Example 6, the electrode plates provided in Examples 1-12 use modified polyurea resin as negative electrode binders, and the negative electrode plates prepared therefrom have a peel strength of up to 17-28N / M, and have excellent flexibility, and the further prepared lithium battery has a first coulomb efficiency of up to 89.5-90.5%, a full-charge expansion rate as low as 27.0-29.2%, and a 500-cycle capacity retention rate of up to 84.6-88.9%, indicating that the present invention has very significant improvements in peel strength, first coulomb efficiency, full-charge expansion, and cycle retention. This shows that the negative electrode binder provided by the present invention has excellent bonding properties, can significantly inhibit the expansion of silicon-based negative electrodes, and at the same time gives the negative electrode plates excellent flexibility, thereby improving the battery's cycle performance.

[0165] Compared with Example 1, in Example 11, since the flexible polyoxyalkylenediamine ED600 is replaced by rigid p-phenylenediamine, when used as a binder, the lack of flexible chain segments leads to reduced peel strength of the electrode and poor flexibility. As the number of cycles increases, the rigid polymer chain cannot adapt to the huge periodic volume changes of silicon particles, and the bonding and restraining effects on the silicon particles gradually deteriorate, resulting in cracking of the negative electrode and peeling of the active coating, resulting in reduced cycle performance.

[0166] Compared with Example 1, in Example 12, since the rigid 4,4′-diphenylmethane diisocyanate (MDI) is replaced by flexible hexamethylene diisocyanate (HDI), when used as a binder, the polymer lacks rigid chain segments, resulting in insufficient mechanical strength of the main chain, reduced peel strength of the electrode, poor flexibility, and inability to maintain the stability of the electrode micro-skeleton structure.

[0167] The effects of Example 11 and Example 12 are slightly worse than that of Example 1. It can be seen that the aqueous polyurea resin containing carbon-carbon double bonds and containing both rigid groups and flexible groups in Example 1 makes the binder flexible, which is beneficial to improving the flexibility of the negative electrode sheet.

[0168] Compared with Example 1, in Comparative Example 1, since the aqueous polyurea resin emulsion containing carbon-carbon double bonds is not added during the preparation of the binder, the binder structure does not contain flexible segments and rigid segments of the polyurea resin, the flexibility of the electrode cannot meet the requirements, and the huge volume change of silicon particles during the charge and discharge process cannot be effectively suppressed, and the peel strength, first coulomb efficiency, full charge expansion and cycle retention rate of the electrode are all reduced.

[0169] Compared with Example 1, in Comparative Example 2, since the acrylic emulsion and the aqueous polyurea resin emulsion containing carbon-carbon double bonds are only physically mixed during the preparation of the binder, the acrylic polymer segment and the polyurea resin segment are not connected by chemical bonds, and the synergistic effect of the acrylic polymer segment and the polyurea resin segment cannot be fully exerted, resulting in a decrease in the peel strength, first coulomb efficiency, full charge expansion and cycle retention rate of the electrode.

[0170] Compared with Example 1, in Comparative Example 3, since the silane coupling agent 3-(acryloyloxy)propyltrimethoxysilane was not added during the preparation of the binder, the prepared modified polyurea resin for the electrode plate did not contain an organic siloxane segment containing a carbon-carbon double bond, and the peel strength, first coulomb efficiency, full charge expansion and cycle retention rate of the plate were all reduced. In addition, since the binder in Comparative Example 3 did not contain an organic silicon group, it could not effectively form strong physical and chemical effects such as hydrogen bonds, ionic bonds, and chemical bonds with the active silicon particles, so the adhesion was reduced and the cycle performance of the battery deteriorated.

[0171] Compared with Example 1, in Comparative Example 4, since the modified polyurea resin (Comparative Example 3) for the electrode plate not containing an organosilicon group is directly physically mixed with 3-(acryloyloxy)propyltrimethoxysilane, the silane coupling agent is not grafted onto the main chain of the binder through chemical bonds to form a side chain, resulting in a decrease in the peel strength, first coulomb efficiency, full charge expansion and cycle retention rate of the electrode plate. The binder cannot effectively stabilize the electrode structure during the charge and discharge process of the silicon-based negative electrode lithium battery, and thus the cycle performance is poor.

[0172] Compared with Example 1, in Comparative Example 5, since only aqueous polyurea resin emulsion containing carbon-carbon double bonds is used as a binder and does not contain acrylic acid, acrylonitrile and silicone grafted units, the peel strength, first coulomb efficiency, full charge expansion and cycle retention rate of the electrode are all reduced.

Claims

1. A lithium battery, characterized in that: It comprises a negative electrode, a positive electrode, an electrolyte and a separator, wherein the negative electrode is an electrode plate, the electrode plate comprises a current collector and a coating, the raw materials for preparing the coating comprise a binder, an active material and a conductive agent, the components of the binder comprise a modified polyurea resin for the electrode plate, the modified polyurea resin for the electrode plate comprises a main chain and a grafting unit, the grafting unit is grafted onto the main chain through a chemical bond, the main chain is an aqueous polyurea resin containing a carbon-carbon double bond, and the grafting unit comprises an acrylonitrile grafting unit, an acrylic grafting unit and an organic siloxane unit containing a carbon-carbon double bond; The aqueous polyurea resin containing carbon-carbon double bonds includes the following preparation raw materials in parts by weight: 10-150 parts of aliphatic polyamines, Aromatic isocyanate 10-80 parts, 2-30 parts of hydrophilic chain extender, 2-20 parts of a capping agent containing a carbon-carbon double bond, 2-30 parts of neutralizer; The aliphatic polyamine is an aliphatic carbon chain diamine and / or an aliphatic ether diamine; The aliphatic carbon chain diamine is at least one of 1,6-hexanediamine, 1,7-heptanediamine, 1,8-octanediamine, 1,9-nonanediamine, 1,10-decanediamine, 1,12-dodecanediamine, 1,14-tetradecanediamine, 1,16-hexadecanediamine, 1,18-octadecanediamine, 1,36-hexatriacontanediamine, and 2,5-dimethyl-1,6-hexanediamine; The aliphatic ether-based diamine is at least one of bis(2-aminoethyl) ether, 3,6-dioxa-1,8-octanediamine, 4,7-dioxa-1,10-decanediamine, 4,7-dioxa-2,9-decanediamine, 4,9-dioxa-1,12-dodecanediamine, 5,8-dioxa-3,10-dodecanediamine, 4,7,10-trioxa-1,13-tridecanediamine, bis(3-aminopropyl)polytetrahydrofuran, and polyoxyalkylenediamine; The hydrophilic chain extender is at least one of 2-carboxyl-1,4-phenylenediamine, 2-amino-5-guanidine valeric acid, 2,6-diaminohexanoic acid, and 2-amino-3-(4-imidazolyl) propionic acid; The capping agent containing a carbon-carbon double bond is at least one of m-isopropenyl-α,α-dimethylphenyl isocyanate, 2-aminoethyl acrylate, and 2-aminoethyl methacrylate.

2. The lithium battery according to claim 1, characterized in that: The method for preparing the modified polyurea resin for the electrode plate comprises the following steps: Mixing an aqueous polyurea resin emulsion containing carbon-carbon double bonds, an acrylonitrile monomer, an acrylic monomer, a silane coupling agent, an emulsifier and an initiator to cause a polymerization reaction to obtain the modified polyurea resin for the electrode plate; The aqueous polyurea resin containing carbon-carbon double bonds comprises the following preparation raw materials in parts by weight: 10-150 parts of aliphatic polyamines, Aromatic isocyanate 10-80 parts, 2-30 parts of hydrophilic chain extender, 2-20 parts of a capping agent containing a carbon-carbon double bond, Neutralizer 2-30 parts.

3. The lithium battery according to claim 1, characterized in that The modified polyurea resin for the electrode plate includes the following raw materials for preparation, in parts by weight: 5-40 parts of water-based polyurea resin emulsion containing carbon-carbon double bonds, 5-40 parts of acrylonitrile monomer, 5-50 parts of acrylic monomer, Silane coupling agent 0.1-30 parts, Emulsifier 0.1-5 parts, Initiator 0.1-5 parts.

4. The lithium battery according to claim 3, characterized in that: The acrylonitrile monomer is acrylonitrile and / or methacrylonitrile.

5. The lithium battery according to claim 3, characterized in that: The acrylic monomer is at least one of acrylic acid, methacrylic acid, lithium acrylate, lithium methacrylate, sodium acrylate, sodium methacrylate, potassium acrylate, and potassium methacrylate.

6. The lithium battery according to claim 3, characterized in that: The silane coupling agent is vinyl trimethoxysilane, vinyl triethoxysilane, vinyl triisopropoxysilane, allyl trimethoxysilane, methyl allyl trimethoxysilane, 3-(acryloxy) propyl trimethoxysilane, 3-(methacryloxy) propyl trimethoxysilane, 3-(acryloxy) propyl methyl dimethoxysilane, 3-(acryloxy) propyl triisopropoxysilane, 3-(acryloxy) propyl methyl diisopropoxysilane, γ-acryloxy propyl tris(β-trimethoxyethoxysilane), 3-(methacryloxy) propyl trimethoxysilane, At least one of 3-(acryloyloxy)propylmethyldimethoxysilane, 3-(acryloyloxy)propyltriethoxysilane, 3-(methacryloyloxy)propyltriethoxysilane, 3-(acryloyloxy)propylmethyldiethoxysilane, 3-(methacryloyloxy)propylmethyldiethoxysilane, 3-(methacryloyloxy)propyltriisopropoxysilane, 3-(methacryloyloxy)propylmethyldiisopropoxysilane, γ-methacryloyloxypropyltris(trimethylsiloxy)silane, and γ-methacryloyloxypropyltris(β-trimethoxyethoxysilane).

7. The lithium battery according to claim 2, characterized in that: The polymerization reaction temperature is 50-90° C., and / or the polymerization reaction time is 2-16 hours.

8. The lithium battery according to claim 1, characterized in that: The method for preparing the electrode sheet comprises the following steps: The binder, active material, conductive agent and water are mixed to obtain electrode slurry, which is then coated on a current collector and dried to obtain a coating to obtain the electrode plate.

Citation Information

Patent Citations

  • Urea-based pressure sensitive adhesives

    CN101925664A

  • Solid electrolyte composition, solid electrolyte-containing sheet and method for producing same, all-solid secondary battery and method for producing same, and polymer and non-aqueous solvent dispersion thereof

    CN110291674A

  • All-solid secondary battery

    JP2011014387A